A Study on Maternal Weight Gain and its Correlation with Birth Weight of Baby at Term - Rijvi, Shiffin; Abbasi, Sharmin; Karmakar, Anuradha; Siddiqua, Sehereen Farhad; Dewan, Farhana (Anwer Khan Modern Medical College Journal, 2018)
Background: Maternal weight gain is influenced by several trends in perinatal health that are of great public health concern. Maternal weight gain during the 2nd and 3rd trimesters is an important determinant of fetal growth Objective: To determine the relationship between maternal weight gain and birth weight of baby at term. Methodology : A cross sectional observational study was carried among 50 pregnant women at term were admitted in the Department of Obstetrics and Gynaecology, Shaheed Suhrawardy Medical College and Hospital and Anwer Khan Modern Medical College hospital during the period of January 2014 to July 2014. Data were collected pre-designed data collection sheet. Results: This study found maximum (36%) were age group 21-25 years followed by 28% were 20 years, 24% were 26-30 years, 8% were 31-35 years and only 4% were 36-40 years. The average age was 25 years. Among these 50 pregnant women, 2 cases (4%) had BMI <18.5, 15 cases (30%) had a BMI 18.5- 24.9, 19 cases (38%) had a BMI 25-29.9 and 14 cases (28%) had a BMI ≥30. The mean birth weight was 2.77±0.33. kg. Mean weight gain was 10.72±3.72 Kg. Weight increased there was a corresponding increase in the mean birth weight and this relationship was statistically significant (<0.05). Conclusion: This study shows maternal weight gain significantly increased birth weight of the baby at term. Maternal weight should continue to be given importance in monitoring the health of pregnancies and bioelectrical impedance analysis and arm measurements should be further investigated as another simple way to track appropriate body composition changes across gestation, especially in resource-limited settings. Although challenging, public health efforts should continue working to improve the nutritional status of women of reproductive age before they conceive as an apparent way to improve birth outcomes. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 22-28